Knowledge and Practice of Dietary Diversity among Pregnant Women: Evaluation of a Large Scale Social and Behaviour Change Program in Bangladesh (Bangladesh Journal of Nutrition, 2021)
The objective of this study was to evaluate the effectiveness of a U.S. Agency for International Development (USAID) supported large-scale social and behaviour change (SBC) intervention, SHIKHA Project, in improving dietary diversity among pregnant women. Cross-sectional survey was conducted in rural southwest Bangladesh and 509, 515, and 1,275 randomly selected pregnant women were interviewed at baseline, midline, and end-line; 514 and 1016 pregnant women from non-intervention areas were also included. SBC intervention was provided to pregnant women at both individual and group levels by trained community health workers during the antenatal and postnatal period. Dietary diversity scores (DDS) and knowledge scores were calculated by summing the number of food groups (from nine defined food groups) consumed by women during 24 hours and from unprompted responses on how many food groups pregnant women should eat. The mean knowledge score for dietary diversity was 5.04 at baseline and significantly increased by 1.68 units (95% CI: 1.51, 1.85) at the end-line. The mean DDS at baseline was 4.28 and significantly increased by 0.45 units (95% CI: 0.34, 0.57) at the end-line. The SBC intervention was effective in improving the dietary diversity of pregnant women, which may help to meet their additional nutritional requirements and improve pregnancy outcomes.Bangladesh J. Nutr. Vol. 34, December 2020, P: 65-75